Environmentally Sensitive Molecular Switches Drive Poplar Phenology - Maurya, Jay P.; Triozzi, Paolo M.; Bhalerao, Rishikesh P.; Perales, Mariano (Frontiers in Plant Science, 2018)
Boreal and temperate woody perennials are highly adapted to their local climate, which delimits the length of the growing period. Moreover, seasonal control of growth-dormancy cycles impacts tree productivity and geographical distribution. Therefore, traits related to phenology are of great interest to tree breeders and particularly relevant in the context of global warming. The recent application of transcriptional profiling and genetic association studies to poplar species has provided a robust molecular framework for investigating molecules with potential links to phenology. The environment dictates phenology by modulating the expression of endogenous molecular switches, the identities of which are currently under investigation. This review outlines the current knowledge of these molecular switches in poplar and covers several perspectives concerning the environmental control of growth-dormancy cycles. In the process, we highlight certain genetic pathways which are affected by short days, low temperatures and cold-induced signaling.